Influence of Overlying Caprock on Coalbed Methane Migration in the Xutuan Coal Mine, Huaibei Coalfield, China: A Conceptional Analysis on Caprock Sealability - Kaizhong Zhang; Qingquan Liu; Kan Jin; Liang Wang; Yuanping Cheng; Qingyi Tu (Geofluids)
In order to determine the controlling factors affecting coalbed gas migration in the Xutuan coal mine, Huaibei Coalfield, China, overlying caprocks with Quaternary and Neogene formation (loose bed), Paleogene formation (Redbed), and coal-bearing strata were investigated via petrography, lithology, and physical properties according to laboratory tests, theoretical analysis, and on-site exploration. Results indicate that the basic properties of coal were not significantly changed whereas the effect of coalbed gas escape was promoted in the presence of Redbed and loose bed. The pore structure analysis shows that Redbed has well-developed pore connectivity than coal-bearing strata (main components are sandstone, siltstone, and mudstone). Also, the diffusion coefficient and permeability of Redbed and loose bed are proved to be a little different than those of sandstone but are much higher than those of mudstone and siltstone. Based on the aforementioned findings, investigation on the sealing mechanism of overlying caprocks on CBM migration was further discussed, interpreting that the thickness, permeation, and diffusion features are crucial factors for sealing capacity of the overlying caprock. Thus, with the simplification on the thickness of overlying strata, a conceptional analysis was carried out to theoretically estimate the sealability of caprocks from surface drilling holes; it appears, though, that the master factor on coalbed methane accumulation is coal-bearing strata instead of Redbed and loose bed with a poor sealability. In this case, the reliability of the evaluation method could be indirectly validated from the on-site gas content data of the actual coal seam to fundamentally reflect the effect of Redbed and loose bed on gas-escaping, and the impact of coal-bearing strata on gas accumulation in the coal seam.